1931
DOI: 10.1104/pp.6.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Strangulation of Cotton Roots

Abstract: In 1923, specimens of a peculiar and, until recently, puzzling cotton root trouble were received. The specimens were of cotton plants with welldeveloped tops but with extremely shallow and very greatly reduced root systems ( fig. 1 a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1957
1957
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…P ANS that restrict plant rooting have been observed in Southern Plains soils for over 40 years (3,4,14,16, and others). These pans affect plant root systems in two general ways.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…P ANS that restrict plant rooting have been observed in Southern Plains soils for over 40 years (3,4,14,16, and others). These pans affect plant root systems in two general ways.…”
mentioning
confidence: 99%
“…These pans affect plant root systems in two general ways. First, plant roots may penetrate the soil pan but are unable to expand their diameter later in the growing season ( 8,14). These pans cause girdled taproots in which transport of water and nutrients is restricted.…”
mentioning
confidence: 99%
“…S EVERAL investigators have shown that soil physical conditions may mechanically impede root development in cotton (1)(2)(3)(4) . In most instances roots were prevented from penetrating through a specific soil zone.…”
mentioning
confidence: 99%
“…In most instances roots were prevented from penetrating through a specific soil zone. However, Taubenhaus et al ( 4) described a soil condition where the cotton roots penetrated but were unable to expand radially within the compacted zone of soil. Lotspeich et al (3) also discussed a somewhat similar phenomenon.…”
mentioning
confidence: 99%
“…Such a layer caused the beets to push out of the ground as they grew, and they were short, giving a low yield with a low sugar content; however, Townsend does not cite data to support the above. Taubenhaus, et al (1931) found that compact soils prevented or seriously affected cotton root penetration in Texas. Phillips (1955) The tubes were watered with nutrient solution periodically and were allowed to drain freely through the bottom, thereby ensuring adequate aeration of the roots.…”
Section: Soil Compaction Aeration and Plant Growthmentioning
confidence: 99%